Mo. Rev. Stat. 854, ch. 47, § 3502 (1889) - (:unkn) unknown (My University, 1889)
Prohibited the concealed carry of any deadly or dangerous weapon or any kind of fire-arms, Bowie-knife, dirk, dagger, slung-shot, or other deadly weapon into any church, or place where people have assembled for religious worship, or into any school room or place where people are assembled for educational, literary, or social purposes, or to any election precinct on election day, into any court-room during the sitting of court, or into any other public assemblage. Also prohibited the brandishing of any above weapons, or carrying above weapon while intoxicated. Also prohibited the transfer of the above weapons to any minor. Violators fined not less than fifty but no more than two hundred dollars, or imprisonment not less than five days but no more than six month.
Keywords: CARRY - CERTAIN PUBLIC PLACES